Coherent transport through a Majorana island in an Aharonov-Bohm interferometer - Whiticar, A. M.; Fornieri, A.; O'Farrell, Eoin; Drachmann, A. C. C.; Wang, T.; Thomas, C.; Gronin, Sergei; Kallaher, Ray; Gardner, Geoff; Manfra, Professor Michael J; Marcus, Charles; Nichele, Fabrizio (Nature Communications, 2020)
Majorana zero modes are leading candidates for topological quantum computation due to non-local qubit encoding and non-abelian exchange statistics. Spatially separated Majorana modes are expected to allow phase-coherent single-electron transport through a topological superconducting island via a mechanism referred to as teleportation. Here we experimentally investigate such a system by patterning an elongated epitaxial InAs-Al island embedded in an Aharonov-Bohm interferometer. With increasing parallel magnetic field, a discrete sub-gap state in the island is lowered to zero energy yielding persistent 1e-periodic Coulomb blockade conductance peaks (e is the elementary charge). In this condition, conductance through the interferometer is observed to oscillate in a perpendicular magnetic field with a flux period of h/e (h is Planck’s constant), indicating coherent transport of single electrons through the islands, a signature of electron teleportation via Majorana modes. Theories predict teleportation of phase-coherent single electrons through a topological superconducting island. Here, the authors report persistent Coulomb blockade conductance peaks due to coherent transport of single electrons through patterned InAs-Al islands embedded in an Aharonov-Bohm interferometer.